Preparation method of carbon quantum dot-polyvinylpyrrolidone-starch composite film and application of carbon quantum dot-polyvinylpyrrolidone-starch composite film in food fresh-keeping storage
By using bagasse carbon quantum dots, polyvinylpyrrolidone and starch to prepare composite films, the challenges of existing environmentally friendly packaging materials in terms of functionality, cost-effectiveness and food safety are solved, and high-performance, low-cost and environmentally friendly food preservation effects are achieved.
Patent Information
- Application Number
- CN202510109798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-11
AI Technical Summary
Existing environmentally friendly packaging materials have challenges in functionality, cost-effectiveness and mass production, and are difficult to ensure food safety.
Baggy cane carbon quantum dots, polyvinylpyrrolidone and starch are used as raw materials. Baggy cane carbon quantum dots are prepared and added to the membrane liquid to form a composite film, which has antibacterial, ultraviolet, antioxidant properties and biodegradability.
It realizes the high performance, low cost and environmental protection of food plastic wrap, extends the shelf life of food, and improves the utilization value of waste biomass, ensuring food safety.
Smart Images

Figure CN119798795A_ABST
Abstract
Description
Technical Field
[0001] The invention specifically relates to a preparation method of a carbon quantum dot-polyvinyl pyrrolidone-starch composite film and application of the composite film in food preservation and storage, belonging to the technical field of preparation of food packaging preservation materials. Background Art
[0002] As people pay more and more attention to environmental protection and health, the pressure caused by traditional plastic packaging materials on the environment due to their non-degradability has attracted increasing attention. Therefore, the development of new environmentally friendly cling film materials has become an urgent need in the food packaging industry. In particular, as the concept of sustainable development has become more popular, the application of bio-based and degradable materials in the field of food packaging has received more and more attention. Existing environmentally friendly packaging materials still face challenges in functionality, cost-effectiveness and large-scale production. For example, some bio-based materials may not be as good as traditional plastics in terms of mechanical properties, barrier properties and stability. Therefore, the development of environmentally friendly packaging materials with excellent performance, especially materials that can improve food preservation and are environmentally friendly, is a technical problem that urgently needs to be solved.
[0003] In recent years, the research on carbon dots (also known as carbon quantum dots, carbon nanodots, CQDs) has become increasingly extensive. For example, studies have shown that carbon dots are used as polymer structure enhancers and bioactive additives in the preparation of food packaging films, playing a variety of functions in food packaging films. Carbon dots are easily combined with polymer material films because their rich surface functional groups can be combined with other compounds through hydrogen bonds, van der Waals interactions or other chemical bonds; due to their unique optical properties and biocompatibility, the application research of carbon dots in food packaging films has made significant progress. This type of functional material has great potential in the food industry.
[0004] At present, the raw materials for the preparation of carbon dots come from a wide range of sources. Adhering to the principles of environmental protection and efficient use of waste, researchers have used biomass raw materials and waste. As a renewable carbon source, biomass is valued for its widespread existence and sustainability in nature. Biomass raw materials include but are not limited to plant straw, wood, animal manure and urban organic waste. They are not only low-cost, but also have the potential to reduce environmental pollution and slow down global warming.
[0005] Although the prior art "CN117825362A A dual-channel intelligent indicator label for monitoring the freshness of high-protein food and its preparation method" discloses: a film is formed by using cassava starch and polyvinyl alcohol as a composite matrix, and loading polyvinyl pyrrolidone-alizarin nanoparticles and carbon quantum dots on the composite matrix in combination with a solvent and / or a film-forming aid, but it is used as an intelligent indicator label, that is, it is used in the detection field; "CN118906564A A starch-polyvinyl alcohol-based film and its preparation method and application" discloses: the first film-forming liquid includes starch, polyvinyl alcohol and a pH fluorescent response material, and the emission fluorescence intensity of the pH fluorescent response material changes with the change of pH value, and the pH fluorescent The response material includes carbon quantum dots, which contain amino and carboxyl groups. The amino and carboxyl groups can undergo protonation / deprotonation reactions when the pH changes, thereby producing different emission fluorescence intensities. Similarly, the film is mainly used in the detection field; and "CN119119660A A UV blocking film and its preparation method and application" discloses that the UV blocking film is made of the following raw materials in weight percentage: polyvinyl alcohol: 20% to 40%; sodium carboxymethyl cellulose: 20% to 30%; carbon quantum dots: 5% to 10%; horseshoe starch: 30% to 45%, but the carbon quantum dots involved are made of waste leather, and food safety cannot be guaranteed (such as: there is chromium in the leather), etc.
[0006] Therefore, a food preservative film having good fresh-keeping performance, being economical and environmentally friendly, and being able to ensure food safety and a preparation method thereof are needed. Summary of the invention
[0007] The present invention provides a composite film-packaging material that is environmentally friendly, has excellent comprehensive performance and is suitable for industrial production while alleviating environmental pressure. In which, sugarcane bagasse waste from sugar factories is used as raw material to prepare sugarcane bagasse carbon quantum dots; then, it is added to a membrane liquid made of polyvinyl pyrrolidone, starch, water and glycerol to prepare a composite film; by combining the advantages of carbon dots and degradable materials (polyvinyl pyrrolidone, starch, water and glycerol), a new packaging material (with antibacterial, anti-ultraviolet, antioxidant properties, biodegradability and other properties) is developed for the food industry, and the value of waste biomass bagasse is increased, that is, a carbon quantum dot-polyvinyl pyrrolidone-starch composite film and its preparation method and application are proposed.
[0008] In order to achieve the above technical objectives, the following technical solutions are proposed: The first purpose of the technical scheme is to: a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, prepared by using bagasse carbon quantum dots, polyvinyl pyrrolidone and starch as raw materials and in the presence of a plasticizer; Among them, the mass proportion of bagasse carbon quantum dots is 0.05-0.25%, the mass proportion of polyvinyl pyrrolidone is 0.5-2.5%, the mass proportion of starch is 0.5-2.5%, and the mass proportion of plasticizer is 0.5-1%; Bagasse carbon quantum dots are prepared from waste bagasse from sugar factories.
[0009] Preferably, the bagasse carbon quantum dots have a size of 3 to 10 nm.
[0010] Preferably, the polyvinyl pyrrolidone is polyvinyl pyrrolidone K90, which is easy to form a film, relatively cheap and has good applicability.
[0011] Preferably, the starch is edible corn starch purchased directly from the market.
[0012] Preferably, the plasticizer is glycerol.
[0013] The second purpose of the technical scheme is: a method for preparing a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, comprising the following steps: S1: Preparation of bagasse carbon quantum dots The waste bagasse from the sugar factory is used as raw material, which is washed, dried at 50-70°C, and crushed into bagasse powder of 50-300 meshes; The obtained bagasse powder is mixed with water at a mass volume ratio of 1:10 to 30, and then placed in a high temperature reaction kettle for hydrothermal reaction at 160 to 220° C. for 2 to 8 hours to obtain a mixed solution; The mixed solution was subjected to ultrasonic treatment for 30 min, filtered using a 0.22 μm water system ultrafiltration membrane, and dialyzed using a 500 Da dialysis bag, the dialyzate was collected, and freeze-dried to obtain bagasse carbon quantum dots; S2: Preparation of bagasse carbon quantum dot solution Dissolving the bagasse carbon quantum dots obtained in step S1 in water to obtain a bagasse carbon quantum dot solution with a concentration of 5 to 10 mg / mL, and storing the solution at 4° C.; S3: Preparation of membrane solution Weigh polyvinyl pyrrolidone, starch, water and plasticizer respectively in the ratio of 0.5-2.5:0.5-2.5:94-98.5:0.5-1, mix evenly, dissolve and gelatinize at 85-95°C for 1-2 hours to obtain a membrane solution; The mass ratio of polyvinyl pyrrolidone to starch is 1-2:1-3, and the amount of plasticizer added is 10-20% of the total amount of polyvinyl pyrrolidone and starch; S4: Preparation of quantum dot-polyvinyl pyrrolidone-starch composite films The bagasse carbon quantum dot solution obtained in step S2 is added to the membrane solution obtained in step S3, and stirred at 85-95° C. for 25-35 minutes to mix evenly; ultrasonic degassing is performed, and the mixture is poured into a molding device, dried at room temperature to form a film, and a composite membrane is obtained.
[0014] The third purpose of the technical solution is to use the carbon quantum dot-polyvinyl pyrrolidone-starch composite film for food packaging and preservation.
[0015] Furthermore, the food packaging has a shelf life of 9 to 15 days.
[0016] In the present technical scheme, since both polyvinyl pyrrolidone and starch are extremely hydrophilic, the compatibility between the two is poor; and when the two are in different proportions, the mechanical properties of the prepared blended film are different. Therefore, before preparing the carbon quantum dot-polyvinyl pyrrolidone-starch functional composite film, the ratio of polyvinyl pyrrolidone and starch is screened, and the ratio of the two is determined by tensile strength and elongation at break; Furthermore, in order to solve the shortcomings of starch film brittleness and poor mechanical properties of polyvinyl pyrrolidone, the technical solution also adds a plasticizer (glycerol), that is, the amount of glycerol added is determined by taking tensile strength and elongation at break as indicators; In addition, when preparing the carbon quantum dot-polyvinyl pyrrolidone-starch functional composite film, firstly, polyvinyl pyrrolidone, starch, water and plasticizer are mixed, and then dissolved and gelatinized at 85-95°C for 1-2h. This operation can fully dissolve polyvinyl pyrrolidone, starch and plasticizer in water, and the three form a uniform membrane liquid, promote the formation of intermolecular interaction between polyvinyl pyrrolidone and starch, and obtain a polyvinyl pyrrolidone-starch system; then, the carbon quantum dot solution is added, and stirred at 85-95°C for 25-35 min, this operation can form hydrogen bonds between the carbon quantum dots and the polyvinyl pyrrolidone-starch system, and make the functional groups on the surface of the carbon quantum dots react with the polyvinyl pyrrolidone-starch system to form chemical bonds, thereby enhancing the stability and mechanical properties of the entire system; finally, the obtained membrane liquid is ultrasonically degassed and poured into a mold to form a film in a windproof manner. This operation can form a uniform mixed liquid among the carbon quantum dots, polyvinyl pyrrolidone and starch, thereby forming a uniform and stable functional composite membrane of carbon quantum dots-polyvinyl pyrrolidone-starch.
[0017] The beneficial technical effects brought about by adopting this technical solution are: 1. The present invention is simple to operate, has a wide range of raw and auxiliary materials, and all of them are renewable resources, has low production cost, is environmentally friendly, and is suitable for large-scale production; Second, in the present invention, the specific ratio of carbon quantum dots, polyvinyl pyrrolidone, starch and plasticizer ensures that the composite film has antibacterial, anti-ultraviolet, antioxidant properties, biodegradability and other properties, and can be specifically used for food preservation; at the same time, it also ensures the tensile strength and elongation at break of the composite film; 3. In the present invention, carbon quantum dots are prepared from waste bagasse from sugar factories, which effectively alleviates environmental pressure and improves the utilization value of waste biomass bagasse. In addition, carbon quantum dots, polyvinyl pyrrolidone and starch are used as the main raw materials. These three raw materials have good biodegradability and are environmentally friendly, effectively reducing the white pollution caused by traditional plastic packaging. 4. In the present invention, the introduction of carbon quantum dots increases the antibacterial properties of the composite film, effectively inhibits the growth of microorganisms on the surface of food, and reduces food spoilage; it also improves the mechanical properties of the composite film and increases its durability; it gives the composite film the ability to block ultraviolet rays, increasing its wide application; it enhances the antioxidant capacity of the composite film, which can have a better preservation effect on food; in addition, the addition of carbon quantum dots enhances the light transmittance of the composite film, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the preparation process of bagasse carbon dots in Example 4; Figure 2 This is the appearance of the bagasse carbon dot solution in Example 4 under natural light and ultraviolet light; Figure 3 It is a physical comparison diagram of the composite films prepared in Examples 4-5 and Comparative Example 1; Figure 4 The antibacterial properties of the composite films prepared in Examples 4-5 and Comparative Example 1; Figure 5 The antioxidant properties of the composite films prepared in Examples 4-5 and Comparative Example 1 (where ABTS and DPPH are commonly used antioxidant determination methods); Figure 6 is the UV blocking ability of the composite films prepared in Examples 4-5 and Comparative Example 1; Figure 7 The pH changes of the composite films prepared in Examples 4-5 and Comparative Example 1 and the commercially available PE films during the storage period of cooked meat; Figure 8 The mechanical properties of the composite films prepared in Examples 4-5 and Comparative Examples 1-3; Fig. 9 To discuss the mechanical properties of the composite films prepared with different ratios of polyvinyl pyrrolidone and starch in Example 1; Fig.10To discuss the mechanical properties of the composite membranes prepared with different addition amounts of glycerol in Example 2; Fig.11 This is a diagram of the equipment layout involved in Example 6; Among them, in the figure: 1. cleaning machine, 2. drying machine, 3. pulverizer, 4. reaction kettle, 5. ultrasonic treatment device, 6. filtering device, 7. dialysis device, 8. freeze-drying device, 9. dissolving device, 10. gelatinization device, 11. mixing device, 12. ultrasonic degassing device, 13. molding device. DETAILED DESCRIPTION
[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The invention is based on current food safety and environmental protection requirements. On the one hand, it provides a food preservative film with excellent performance, and on the other hand, it ensures that the food preservative film is suitable for industrial production, that is, the raw material cost involved is low, the preparation process is simple, etc.; at the same time, it provides a way to recycle sugarcane bagasse.
[0021] For example, the prior art publicly uses citric acid, p-phenylenediamine, garlic and other raw materials to prepare carbon quantum dots, but they mainly use the fluorescence and adsorption of carbon quantum dots in the field of photocatalysis, degradation of organic pollution in water, sensors and ion detection. The present invention uses bagasse carbon quantum dots to provide a channel for the reuse of bagasse, and bagasse is low-cost and sustainable, and contains rich organic matter such as cellulose, hemicellulose and lignin; the preparation process involved is simple, and the prepared carbon dots have good biocompatibility and water solubility, showing good functional properties, and are suitable for the preparation of food cling film in terms of economic cost and use.
[0022] The present invention uses traditional biomass waste - bagasse, to turn waste into treasure, and can be used as a raw material to extend the shelf life of food. Preservation mechanism: bagasse carbon quantum dots, polyvinyl pyrrolidone and starch are used to prepare a composite film. The three are mixed to form an intermolecular force, which can improve the mechanical properties of the film and protect food from physical damage; the addition of bagasse carbon quantum dots enhances the ultraviolet absorption and antioxidant properties of the film, and the rich functional groups on the surface of bagasse carbon quantum dots interact with bacteria to achieve an antibacterial effect, increase antibacterial properties, and extend the shelf life of food.
[0023] This is illustrated by the following example.
[0024] Example 1 This embodiment provides: a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, which is prepared using bagasse carbon quantum dots, polyvinyl pyrrolidone and starch as raw materials under the action of a plasticizer; Among them, the mass proportion of bagasse carbon quantum dots is 0.05-0.25%, the mass proportion of polyvinyl pyrrolidone is 0.5-2.5%, the mass proportion of starch is 0.5-2.5%, and the mass proportion of plasticizer is 0.5-1%; Bagasse carbon quantum dots are prepared from waste bagasse from sugar factories. The size of bagasse carbon quantum dots is 3-10nm. The polyvinyl pyrrolidone is polyvinyl pyrrolidone K90, which is easy to form a film, relatively cheap and has good applicability; Starch is edible corn starch purchased directly from the market; The plasticizer is glycerol.
[0025] Example 2 This embodiment provides: a method for preparing a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, comprising the following steps: S1: Preparation of bagasse carbon quantum dots The waste bagasse from the sugar factory is used as raw material, which is washed, dried at 50-70°C, and crushed into bagasse powder of 50-300 meshes; The obtained bagasse powder is mixed with water at a mass volume ratio of 1:10 to 30, and then placed in a high temperature reaction kettle for hydrothermal reaction at 160 to 220° C. for 2 to 8 hours to obtain a mixed solution; The mixed solution was subjected to ultrasonic treatment for 30 min, filtered using a 0.22 μm water system ultrafiltration membrane, and dialyzed using a 500 Da dialysis bag, the dialyzate was collected, and freeze-dried to obtain bagasse carbon quantum dots; S2: Preparation of bagasse carbon quantum dot solution Dissolving the bagasse carbon quantum dots obtained in step S1 in water to obtain a carbon quantum dot solution with a concentration of 5 to 10 mg / mL, and storing the solution at 4° C.; S3: Preparation of membrane solution Weigh polyvinyl pyrrolidone, starch, water and plasticizer respectively in the ratio of 0.5-2.5:0.5-2.5:94-98.5:0.5-1, mix evenly, dissolve and gelatinize at 85-95°C for 1-2 hours to obtain a membrane solution; The mass ratio of polyvinyl pyrrolidone to starch is 1-2:1-3, and the amount of plasticizer added is 10-20% of the total amount of polyvinyl pyrrolidone and starch; S4: Preparation of quantum dot-polyvinyl pyrrolidone-starch composite films The bagasse carbon quantum dot solution obtained in step S2 is added to the membrane solution obtained in step S3, and stirred at 85-95° C. for 25-35 minutes to mix evenly; ultrasonic degassing is performed, and the mixture is poured into a molding device, dried at room temperature to form a film, and a composite membrane is obtained.
[0026] Example 3 On the basis of Example 1-2, this example uses the carbon quantum dot-polyvinyl pyrrolidone-starch composite film for food packaging and preservation.
[0027] Among them, the shelf life of food packaging is 9 to 15 days.
[0028] Example 4 This embodiment provides a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, such as Figure 1 As shown, the specific preparation steps involved are as follows: 1) Select the discarded bagasse from the sugar factory as the raw material, wash it with clean water, dry it at 60℃, crush it, pass it through a 100-mesh sieve, and set it aside; 2) Mix the sieved bagasse powder and water (preferably deionized water) in a mass volume ratio of 1:30; place in a high temperature reactor for hydrothermal reaction at 180°C for 6 hours, cool to room temperature, and take out to obtain a mixed solution; 3) The mixed solution was ultrasonically treated for 30 min, filtered with a 0.22 µm water microfiltration membrane (to remove large particle impurities), and the filtrate was dialyzed with a 500 Da dialysis bag (to remove small molecular impurities); then, freeze-dried to obtain sugarcane bagasse carbon quantum dots; 4) Dissolve bagasse carbon quantum dots in water to prepare a bagasse carbon dot solution with a concentration of 5 mg / mL. The obtained bagasse carbon dot solution was placed under natural light and ultraviolet light respectively. Figure 2 As shown; 5) The membrane solution was prepared according to the following mass ratio: 0.05% of bagasse carbon quantum dots, 5% of polyvinyl pyrrolidone and corn starch (mass ratio 1:1), 1% of glycerol, and the rest was water (i.e., 93.95%); Polyvinyl pyrrolidone, corn starch, glycerol and water were mixed evenly, dissolved and gelatinized at 90°C for 2 hours to obtain a membrane solution; 6) Add the obtained bagasse carbon quantum dot solution to the obtained membrane solution, stir at 90°C for 25 minutes, mix evenly, degas by ultrasonic, pour into a molding device, dry at room temperature to form a film, and obtain a composite membrane (such as Figure 3 as shown).
[0029] Example 5 On the basis of Example 4, the difference between this example and Example 4 is that: when preparing the membrane solution, the sugarcane bagasse carbon quantum dots account for 0.25% (that is, the water accounts for 93.75%), and the rest is the same as Example 4. Finally, the obtained composite membrane is as follows Figure 3 shown.
[0030] Example 6 On the basis of Examples 1-5, this example provides a system for preparing carbon quantum dots-polyvinyl pyrrolidone-starch composite films to cooperate with the preparation process of carbon quantum dots-polyvinyl pyrrolidone-starch composite films, ultimately achieving the comprehensive utilization of waste bagasse from sugar factories, and ensuring the industrial production of carbon quantum dots-polyvinyl pyrrolidone-starch composite films.
[0031] The details are as follows: A preparation system of a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, such as Fig.11 As shown, it includes a bagasse carbon quantum dot preparation subsystem, a membrane liquid preparation subsystem, a dissolving device 9, a mixing device 11, an ultrasonic degassing device 12 and a molding device 13; The bagasse carbon quantum dot preparation subsystem includes a cleaning machine 1, a drying machine 2, a pulverizer 3, a reactor 4, an ultrasonic treatment device 5, a filtering device 6, a dialysis device 7 and a freeze-drying device 8. The cleaning machine 1 is provided with a bagasse feed port, and the bagasse discharge port on the cleaning machine 1 is connected to the feed port of the drying machine 2; the pulverizer 3 is arranged at the rear side of the station of the drying machine 2, and the drying machine 2 is connected to the pulverizer 3; the reactor 4 is arranged at the rear side of the station of the pulverizer 3, and the pulverizer 3 is connected to the reactor 4, and the reactor 4 is connected to a water inlet pipe I; the ultrasonic treatment device 5 is arranged at the rear side of the station of the reactor 4 At the rear side of the station, the reactor 4 is connected to the ultrasonic treatment device 5; the filtering device 6 is arranged at the rear side of the station of the ultrasonic treatment device 5, and the ultrasonic treatment device 5 is connected to the filtering device 6; the dialysis device 7 is arranged at the rear side of the station of the filtering device 6, and the filtering device 6 is connected to the dialysis device 7; the freeze drying device 8 is arranged at the rear side of the station of the dialysis device 7, and the dialysis device 7 is connected to the freeze drying device 8, and a continuous passage for preparing bagasse carbon quantum dots is formed between the cleaning machine 1, the drying machine 2, the pulverizer 3, the reactor 4, the ultrasonic treatment device 5, the dialysis device 7 and the freeze drying device 8; The dissolving device 9 is arranged at the rear side of the station of the freeze drying device 8, and the freeze drying device 8 is connected to the dissolving device 9; The membrane liquid preparation subsystem includes a gelatinization device 10, and the gelatinization device 10 is connected with a polyvinyl pyrrolidone inlet pipe, a starch inlet pipe, a water inlet pipe II and a plasticizer inlet pipe; The discharge port of the gelatinization device 10 is connected to the mixing device 11 , the discharge port of the dissolving device 9 is connected to the mixing device 11 , the discharge port of the mixing device 11 is connected to the ultrasonic degassing device 12 , and the discharge port of the ultrasonic degassing device 12 is connected to the molding device 13 .
[0032] In addition, corresponding stirring mechanisms and temperature regulating devices may be further provided according to actual needs, for example, in order to ensure the reaction efficiency and quality in the reactor 4, a stirring mechanism may be provided in the reactor 4, and a heating jacket may be provided on the outside of the reactor 4; in order to ensure the gelatinization efficiency and quality in the gelatinization device 10, a stirring mechanism may be provided in the gelatinization device 10, and a heating jacket may be provided on the outside of the gelatinization device 10; In addition, temperature sensors are provided at corresponding temperature control locations, and regulating valves or metering pumps are added to corresponding feed pipes and discharge pipes.
[0033] The filtration device 6 is provided with a 0.22 μm water system ultrafiltration membrane, and the dialysis device 7 is provided with a 500 Da dialysis bag.
[0034] Comparative Example 1 On the basis of Example 4, when preparing the composite membrane, the difference between this comparative example and Example 4 is that no bagasse carbon quantum dots are added, and the rest is the same as Example 4. Finally, the obtained composite membrane is as follows Figure 3 shown.
[0035] Based on Examples 4-5 and Comparative Example 1, a performance test was performed, and the specific process is as follows: 1. Antibacterial performance test Escherichia coli and Staphylococcus aureus were used as test bacteria, and the antibacterial test was performed using the agar punching method. Pour the sterilized culture medium into the culture dish on the clean bench, shake it horizontally to make a flat plate, use a pipette to suck 0.1mL of bacterial solution and spread it on the plate, and after cooling and solidification, punch a 6 mm hole on the plate, suck 0.1mL of sterilized membrane solution into the hole, place it in a 37℃ constant temperature box for cultivation, observe the bacterial growth, and measure the diameter of the antibacterial zone using the cross method. Repeat the measurement three times and take the average value to obtain the antibacterial result; The results are as follows Figure 4 As shown, pure polyvinyl pyrrolidone starch has no inhibitory effect on Escherichia coli and Staphylococcus aureus. Bacteria are formed around the holes because starch and polyvinyl pyrrolidone themselves have no antibacterial ability. After adding sugarcane bagasse carbon dots, the diameter of the inhibition zone increased significantly, indicating that carbon dots play a role in antibacterial. This is because small-sized carbon dots can effectively bind to the cell membrane and destroy the cell structure. After entering the cell, carbon dots may also destroy bacterial proteins and nucleic acids, causing bacterial death. Therefore, the addition of carbon dots increases the antibacterial properties of the film.
[0036] 2. Antioxidant performance test 1. DPPH free radical scavenging test Take 0.1g of film sample and mix with 4mL of DPPH working solution, and react for 20min in the dark. The absorbance at 517nm is measured and recorded as A1. The free radical scavenging ability is calculated as follows: DPPH free radical scavenging rate (%) = ; in, A 0 is the absorbance of the control group, A 1 is the absorbance of the sample solution.
[0037] 2. ABTS •+ Free radical scavenging assay Take 0.1 g of film sample and 4 mL of ABTS •+ The working solution was mixed and reacted for 5 minutes, and its absorbance was measured. The free radical scavenging ability was calculated as follows: ABTS •+ Free radical scavenging rate (%) = ; in, A 0 is the absorbance of the control group, A 1 is the absorbance of the sample solution.
[0038] The results are as follows Figure 5 As shown in the figure, it can be seen that pure polyvinyl pyrrolidone-starch film has a strong effect on DPPH and ABTS •+ The free radical scavenging rate is extremely low. After adding bagasse carbon dots, it increases with the increase of bagasse carbon dot concentration, indicating that the addition of carbon dots enhances the antioxidant properties of the film. This is because the carbon dots after hydrothermal treatment have abundant oxygen-containing functional groups such as carboxyl groups, which can act as proton donors to enhance their free radical scavenging ability. It is the addition of carbon dots that enhances the antioxidant capacity of the film.
[0039] 3. Conduct UV blocking ability test Use a UV-visible spectrophotometer to record the UV absorption spectrum of the sample at 200-800nm; The results are as follows Figure 6 As shown, it can be seen that ultraviolet light mainly exists in 200-400nm. Figure 6 It can be seen that with the increase of carbon dots, the UV transmittance at 200-300nm gradually decreases, mainly due to the π-π * Transition and n-π * Transitions, these transition processes enable carbon dots to effectively absorb ultraviolet light, and the addition of carbon dots enhances the ultraviolet blocking ability of the film.
[0040] 4. Carry out freshness preservation performance test Four portions of cooked beef (same freshness) were taken and wrapped with the PE films of Examples 4-5, Comparative Example 1 and commercially available, respectively, and stored in a refrigerator at 4°C. As the storage time increased, the physical and chemical indices of the preserved cooked beef were tested to evaluate the preservation effect.
[0041] The results are as follows Figure 7 As shown, it can be seen that: with the increase of storage time, the pH value of cooked beef increases, and when the pH value is greater than 6.7, the meat is judged to have deteriorated. This shows that the composite film provided by the present invention can slow down the deterioration of meat and extend the storage period.
[0042] Comparative Example 2 On the basis of Example 4, when preparing the composite membrane, the difference between this comparative example and Example 4 is that glycerol is not added, and the rest is the same as Example 4.
[0043] Comparative Example 3 On the basis of Example 4, when preparing the composite membrane, the difference between this comparative example and Example 4 is that no bagasse carbon quantum dots and glycerol are added, and the rest is the same as Example 4.
[0044] Based on Examples 4-5 and Comparative Examples 1-3, tensile strength and elongation at break performance tests were performed, and the specific process included: cutting the sample film into 5 mm strips, measuring the tensile strength and elongation at break using an A1-7000S tensile measuring machine, and measuring each sample film three times; The results are as follows Figure 8 As shown, it can be seen that the addition of bagasse carbon dots has greatly changed the mechanical properties of the composite film, indicating that hydrogen bonds or other chemical bonds are formed between the bagasse carbon dots and the polyvinyl pyrrolidone-starch-glycerol system, which enhances the performance of the composite film. The results show that the effect of missing any system is not ideal.
[0045] Discussion Example 1 On the basis of Comparative Example 3 (without adding bagasse carbon quantum dots and glycerol), this paper discusses polyvinyl pyrrolidone and corn starch at different mass ratios, respectively, for preparing composite films, and then the mechanical properties of the composite films are measured: the tensile strength and elongation at break are measured by an A1-7000S tensile measuring machine, and each composite film is measured three times; The results are as follows Fig. 9 As shown, it can be seen that the tensile strength of the combination of pure corn starch and PVA is greater than the national standard requirement (>10MPa). Since corn starch has certain brittleness and water absorption characteristics, considering the comprehensive elongation at break, the mass ratio of polyvinyl pyrrolidone to starch is 1-2:1-3 for the preparation of composite film.
[0046] Discussion Example 2 On the basis of comparative example 1 (without adding bagasse carbon quantum dots), the mass ratio of polyvinyl pyrrolidone to corn starch was selected to be 1:1, and the amount of glycerol added accounted for 0-50% of the total mass of polyvinyl pyrrolidone and corn starch. The preparation of composite films using different amounts of glycerol was discussed, and then the mechanical properties of the composite films were measured: the tensile strength and elongation at break were measured by an A1-7000S tensile measuring machine, and each film was measured three times; The results are as follows Fig.10 As shown, it can be seen that the addition of glycerol has a great influence on the mechanical properties of the film. With the increase of glycerol, the tensile strength gradually decreases, and the elongation at break shows a trend of first increasing and then decreasing. Taking comprehensive considerations, the final glycerol addition amount is selected to be 10-20% of the total mass of polyvinyl pyrrolidone and corn starch.
Claims
1. A carbon quantum dot-polyvinyl pyrrolidone-starch composite film, characterized in that: It is prepared with bagasse carbon quantum dots, polyvinyl pyrrolidone and starch as raw materials, supplemented with plasticizer; Among them, the mass proportion of bagasse carbon quantum dots is 0.05-0.25%, the mass proportion of polyvinyl pyrrolidone is 0.5-2.5%, the mass proportion of starch is 0.5-2.5%, and the mass proportion of plasticizer is 0.5-1%; Bagasse carbon quantum dots are prepared using bagasse waste from sugar factories as raw materials.
2. The carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 1, characterized in that: The carbon quantum dots have a size of 3 to 10 nm.
3. The carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 1, characterized in that The polyvinyl pyrrolidone is polyvinyl pyrrolidone K90.
4. The carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 1, characterized in that The plasticizer is glycerol.
5. A method for preparing a carbon quantum dot-polyvinyl pyrrolidone-starch composite film, characterized in that: The preparation method of the carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to any one of claims 1 to 4 comprises the following steps: S1: Preparation of bagasse carbon quantum dots Using the discarded bagasse from the sugar factory as raw material, washing, drying and crushing to obtain bagasse powder; The obtained bagasse powder is mixed with water, placed in a high temperature reactor, and subjected to hydrothermal reaction at 160-220° C. for 2-8 hours to obtain a mixed solution; The mixed solution is subjected to ultrasonic treatment, filtration and dialyzation in sequence, the dialyzate is collected and freeze-dried to obtain bagasse carbon quantum dots; S2: Preparation of bagasse carbon quantum dot solution Dissolving the bagasse carbon quantum dots obtained in step S1 in water to obtain a carbon quantum dot solution with a concentration of 5 to 10 mg / mL, and storing the solution at 4° C.; S3: Preparation of membrane solution Weigh polyvinyl pyrrolidone, starch, water and plasticizer respectively in the ratio of 0.5-2.5:0.5-2.5:94-98.5:0.5-1, mix evenly, dissolve and gelatinize at 85-95°C to obtain membrane solution; The mass ratio of polyvinyl pyrrolidone to starch is 1-2:1-3, and the amount of plasticizer added is 10-20% of the total amount of polyvinyl pyrrolidone and starch; S4: Preparation of quantum dot-polyvinyl pyrrolidone-starch composite films The carbon quantum dot solution obtained in step S2 is added to the membrane solution obtained in step S3, and stirred at 85-95° C. for 25-35 minutes to mix evenly; ultrasonic degassing is performed, and the mixture is poured into a molding device, and dried at room temperature to form a film to obtain a composite membrane.
6. The method for preparing the carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 5, characterized in that: In step S1, the bagasse is washed, dried at 50-70° C., and crushed into bagasse powder of 50-300 meshes; When bagasse powder is mixed with water, the mass volume ratio of the two is 1:10-30.
7. The method for preparing the carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 6, characterized in that: In step S1, during filtration, a water-based ultrafiltration membrane with a pore size of 0.22 μm is used; during dialysis, a 500 Da dialysis bag is used.
8. The method for preparing the carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to claim 7, characterized in that: In step S3, dissolution and gelatinization are performed for 1 to 2 hours.
9. The carbon quantum dot-polyvinyl pyrrolidone-starch composite film according to any one of claims 1 to 4, or the carbon quantum dot-polyvinyl pyrrolidone-starch composite film prepared by the preparation method according to any one of claims 5 to 8, is applied to food packaging and preservation.
10. The use according to claim 9, characterized in that: The food packaging has a fresh-keeping time of 9 to 15 days.
Citation Information
Patent Citations
Starch-polyvinyl alcohol-based film as well as preparation method and application thereof
CN118906564A
High-heat-dissipation carbon quantum dot fluorescent composite film and preparation method thereof
CN113583275A
Carboxymethyl starch / chitosan / PVP (Polyvinyl Pyrrolidone) composite membrane as well as preparation method and application thereof
CN115286826A
Indicating label for intelligently monitoring freshness of high-protein food through two channels and preparation method of indicating label
CN117825362A
Preparation method and application of degradable preservative film based on walnut green seedcase
CN118344631A
Cited By
Carbon quantum dot-polyvinyl alcohol composite film as well as preparation method and application thereof
CN120966172A